Detection and Stimulation of Growth and Developmental in Children with Developmental Delay in Tegal City - Ratih Sakti Prastiwi (Alma Ata University Press, 2020)
Homeschooling was one of informal education as an alternative for children with developmental delay who could not follow a formal school system. Homeschooling had a unique method of teaching their students based on their ability so they could explore their ability and their interest. This study aimed to identify the strategy to detect and stimulate children with developmental delay in Tegal City. This study was a qualitative study with a phenomenology approach. The researcher used snowball sampling and human instrument in collecting data. The researcher did data reduction, data display, and made the decision. The triangulation of methods verified the data. The result shows that growth and development detection carried out by teachers since student entrance selection and during learning in class. Stimulation carried out by teachers by focusing on one ability so that children could mastering them. Stimulation focus on cognitive ability and for other ability carried out by professionals such as doctors or therapies.